The effect of self-efficacy and job attachment on employee performance with job satisfaction as an intervening variable in employees of PT Belitang Panen Raya Ogan Komering Ulu Timur - Sindyania, Sindyania; Widiyanti, Marlina; Hadjri, Muhammad Ichsan; Karimudin, Yos; Hanafi, Agustina (Gema Wiralodra, 2024)
This research aims to determine the influence of self-efficacy and work engagement on employee performance with job satisfaction as an intervening variable at PT Belitang Panen Raya Ogan Komering Ulu Timur employees. This research includes quantitative research. The research sample was 109 active employees at PT Belitang Panen Raya. Data collection techniques were carried out by providing self-efficacy questionnaires, work engagement, employee performance questionnaires and job satisfaction. The data analysis method in this research is Structural Equation Modeling (SEM) using the SmartPLS application. The results of this research show that self-efficacy has a positive and significant effect on the performance of PT Belitang Panen Raya employees. Work engagement has a negative and insignificant effect on the performance of PT Belitang Panen Raya employees. Job satisfaction has a positive and significant effect on the performance of PT Belitang Panen Raya employees. Self-efficacy has a positive and significant effect on the performance of PT employees. Belitang Panen Raya through job satisfaction as an intervening variable. Work engagement has a positive and significant effect on the performance of PT employees. Belitang Panen Raya through job satisfaction as an intervening variable